Financial monitoring of payment card transactions - Vnukova, N.; Avanesian, V. (My University, 2022)
The relevance of determining the impact of international standards on the development of financial investigations is determined by the need to build an effective financial monitoring system and improve the effectiveness of coordination of the activities of financial monitoring entities, in particular, at the state level. The aim of the study is to develop theoretical provisions and practical skills to determine the essence of financial monitoring and development of the direction of financial investigations to counter money-laundering and the financing of terrorism. It has been established that cash is widespread in criminal money laundering schemes. In the context of a sufficiently large amount of cash in the economy, which is used on a scale taking into account the nature and specifics of their activities, identifying and combatting money-laundering of criminal proceeds using cash is a difficult task. Given the constant introduction of legislative restrictions and increased control of the financial system by public authorities, intruders are developing new or improving existing money laundering schemes, aiming to give illegal financial transactions the most legal appearance. At the same time, both at the level of public authorities and at the level of primary financial monitoring entities, new methods and approaches to identifying money laundering schemes are constantly being introduced and improved. The organization of financial investigations has become more important since the introduction of international FATF standards
Keywords: The State Financial Monitoring Service; «dirty» money; money laundering; Financial Action Task Force; cash